Occupational Allergic Contact Dermatitis Caused by Epoxy Resin in the Centre of Portugal - Ferreira Bastos, Mariana (2019)
Introduction. Occupational Allergic Contact Dermatitis is a very common occupational disease and epoxy resins are among its main causes. The aim of this study was to characterize patients with positive patch test reactions to epoxy resin detected in the Coimbra Hospital and University Center between 2012 and 2018 and compare with the results of patients patch tested between 1999 and 2008 at the same Institution. Method and Materials.  Within aretrospective analysis of the files of patients with positive patch test reactions (1+ or more intense) to epoxy resin of bisfenol A tested at 1% pet. within the Baseline Series between 2012 and 2018, we characterized demographic and clinical data of reactive patients, evaluated the relevance of the reaction, sources of exposure to epoxy resin with particular attention to occupational exposures, other positive reactions and the impact of the results of the tests in the work conditions of these patients. Lastly, we compared these results with a previous study performed in the same Hospital between 1999 and 2008. Results. Among 2363 patch tested patients during the study period we found 23 patients (0.97%), 17 males and 6 females, who developed contact allergy to epoxy resins. In 22 cases we identified a relevant occupational exposure: 9 from construction industry; 9 workers from wind-mill turbines factory for Eolic energy; 2 from fiberglass factories; 1 from a chemical factory and 1 from a Wastewater Treatment Plant. In 1 patient (a teacher) no relevance was found. Of these 22 workers, 9 (39.1%) had both hand and airborne lesions, while 8 (34.8%) had lesions exclusively on the hands and 5 (21.7%) had predominately airborne dermatitis. Four of the 23 (17.4%) reacted exclusively to the epoxy resin, and 11 of 18 (61.1%) also reacted to 0.25% hexanediol diglycidyl ether. Avoidance resulted in a significant improvement of symptoms. Compared to the previous period (1999-2008), there are no significative changes apart from a slight increase in the frequency of the allergic reactions to epoxy resins and its main source of exposure. Conclusions. The prevalence of allergic contact dermatitis to epoxy resin has slightly increased in this Portuguese Center mostly due to workers from wind-mill turbines factory for Eolic energy, a recent industry implanted in this region. This allergen still causes almost exclusively occupational dermatitis, either hand, airborne, or both.